Comparison of Histochemical Stainings in Evaluation of Liver Fibrosis and Correlation with Transient Elastography in Chronic Hepatitis. (17th November 2015) - Cabibi, Daniela; Bronte, Fabrizio; Porcasi, Rossana; Ingrao, Sabrina; Giannone, Antonino Giulio; Maida, Marcello; Grazia Bavetta, Maria; Petta, Salvatore; Di Marco, Vito; Calvaruso, Vincenza
Abstract : Background and Aim . The best staining to evaluate liver fibrosis in liver hepatitis is still a debated topic. This study aimed to compare Masson's trichrome (MT), Sirius Red (SR), and orcein stainings in evaluating liver fibrosis in chronic HCV hepatitis (CHC) with semiquantitative and quantitative methods (Collagen Proportionate Area (CPA) by Digital Image Analysis (DIA)) and correlate them with transient elastography (TE). Methods . Liver stiffness evaluation of 111 consecutive patients with CHC was performed by TE. Semiquantitative staging by Metavir score system and CPA by DIA were assessed on liver biopsy stained with MT, SR, and orcein. Results . MT, SR, and orcein staining showed concordant results in 89.6% of cases in staging CHC, without significant difference in both semiquantitative and quantitative evaluations of fibrosis. TE values were concordant with orcein levels in 86.5% of the cases and with MT/RS in 77.5% (P < 0.001 ). No significant correlation between the grade of necroinflammatory activity and TE values was found. Conclusion . In CHC, SR/MT and orcein stainings are almost concordant and when discordant, orcein staining is better related to TE values than MT/RS. This suggests that elastic fibers play a more important role than reticular or collagenous ones in determining stiffness values in CHC.